Anodization Behavior of Glassy Metallic Hafnium Thin Films. Issue 4 (1st January 2015) - Mardare, Andrei Ionut; Siket, Christian M.; Gavrilović-Wohlmuther, Aleksandra; Kleber, Christoph; Bauer, Siegfried; Hassel, Achim Walter
Abstract : Glassy metallic Hf thin films were obtained using electron beam deposition at room temperature due to the low energy received by Hf atoms during the film formation process. The amorphous nature of the Hf films suggested by XRD was confirmed by low temperature electrical conductivity measurements where a negative temperature coefficient of resistivity was identified. Anodic oxidations using a scanning droplet cell microscopy were performed on a typical crystalline (hexagonal) Hf film obtained by sputtering and on the glassy Hf. A decrease of the oxide formation factor by 30% (from 2.4 to 1.7 nm V −1 ) was evidenced on the amorphous Hf. Electrochemical impedance spectroscopy on both samples revealed almost identical capacitances while the electrical permittivities were found to differ by 40%. The dielectric constant of the HfO2 decreased from 33.5 on the crystalline parent metal sample to 19.8 on the amorphous one. The unexpected 10% deviation was attributed to a smoother defect-free oxide/metal interface in the case of HfO2 grown on glassy Hf film.